A longitudinal comparison in cynomolgus macaques of the effect of brimonidine on optic nerve neuropathy using diffusion tensor imaging magnetic resonance imaging and spectral domain optical coherence tomography. Issue 4 (April 2021) - Takahashi, Nobuyuki; Matsunaga, Naoko; Natsume, Takahiro; Kitazawa, Chinatsu; Itani, Yoshitaka; Hama, Aldric; Hayashi, Ikuo; Shimazawa, Masamitsu; Hara, Hideaki; Takamatsu, Hiroyuki
Abstract: Early detection of optic neuropathy is crucial for initiating treatment that could delay or prevent visual field loss. Preclinical studies have advanced a number of potential neuroprotective strategies to prevent retinal ganglion cell (RGC) degeneration, but none have successfully completed clinical trials. One issue related to the lack of preclinical to clinical translation is the lack of preclinical morphometric assessments that could be used to track neuroprotection, as well as neurodegeneration, over time within the same animal. Thus, to assess whether clinically used morphometric assessments can identify neuroprotection of RGC, the current study compared optic nerve fractional anisotropy (FA) obtained with diffusion tensor imaging (DTI) and retinal nerve fiber layer (RNFL) thickness measured with spectral domain optical coherence tomography (SD-OCT) to observe not only the early progression of RGC axonal degeneration but to also discern which imaging modality identifies signs of neuroprotection during treatment with the alpha-adrenoceptor agonist brimonidine. Elevated and sustained intraocular pressure (IOP) was observed following laser photocoagulation of the trabecular meshwork in one eye of nonhuman primates (NHP). Either brimonidine (0.1%) or control treatment was instilled twice daily for two months. In control-treated eyes, increased IOP, increased vertical cup-to-disc (C/D), reduced rim-to-disc (R/D) ratio, decreased RNFL thickness and decreased FA were observed. While IOP remained elevated during the course of the study, brimonidine tended to delay the progression of RNFL thinning. However, in the same animal, optic nerve FA did not appear to decline. Brimonidine treatment did not affect other measures of RGC axonal degeneration. The current findings demonstrate that early progression of optic neuropathy can be tracked over time in a nonhuman primate model of ocular hypertension using either DTI or SD-OCT. Furthermore, the delayed changes to RNFL thickness and FA appear to be a neuroprotective effect of brimonidine independent of its effect on IOP. Abstract : laser-induced ocular hypertension; optic nerve fractional anisotropy; retinal nerve fiber layer thickness; diffusion tensor imaging-magnetic resonance imaging; spectral domain optic coherence tomography; neuroprotection.